The Effect of Board of Directors’ Characteristics on the Financial Performance of Saudi Industrial Corporations: An Empirical Study - Alsayegh, Maha Faisal; Baaqeel, Fatmah Mohammad (Journal of Economic, Administrative and Legal Sciences, 2023)
This research aimed to examine the effect of board of directors’ characteristics on the financial performance of Saudi industrial corporations. The sample consisted of 40 corporations listed under material sector on Saudi Stock Exchange (Tadawul) for a five-year period (2017 – 2021). Four of board of directors’ characteristics were examined exemplified in board size, board meetings, board independence and board education. The performance was measured by return on assets (ROA), return on equity (ROE) and Tobin’s Q (TQ). Using panel data method in analyzing data, the findings indicated that there is no significant effect from the previously listed board of directors’ characteristics on the three measurements of performance. The study recommended the following: a) the appointing of board of directors should be based on an objective criterion specially for the independent members and the members with high educational qualifications who should have the required experience for achieving companies’ goals; b) that the Capital Market Authority should give more importance to both quantity and quality aspects of board of directors’ characteristics and to conduct researches related to it.